Proceso de fidelización al cliente de la empresa de Servicios Red Nueva Conexión del cantón Puebloviejo. - Muñoz Alcívar, Juliana Jusleydi (2022)
The incursion of new competitors has led companies to design modern methods and strategies that allow them to retain their existing customers as a way to guarantee the growth of their sales, therefore, this study is developed with the objective of analyzing the procedures develops to retain customers of the company Red Nueva Conexión of the Puebloviejo canton, in addition, the line of research "Information and communication systems, entrepreneurship and innovation" and the subline "marketing and commercialization" are considered. The methodology for carrying out the research includes the descriptive method, it allows discovering the degree of satisfaction obtained with the acquisition of the services and the information gathering techniques are used: interview and survey, and the instruments: interview questionnaire applied to the company administrator and two survey forms, one applied to all internal customers and the other modified to a random sample of 30 external customers. The results obtained allow us to determine that the company has problems of lack of knowledge and commitment to execute the marketing and sales strategies of the staff. By virtue of what has been obtained, it can be elucidated that the study has allowed knowing the processes that affect customer loyalty that the service company of Red Nueva Conexión of the Puebloviejo canton develops, the same ones that show the lack of structuring as a general problem. of a strategic plan aimed at the efficient use of resources.